2016
DOI: 10.1016/j.abrep.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Traits associated with internet addiction in young adults: Potential risk factors

Abstract: The present study sought to determine whether certain personality traits associated with problematic substance use may also characterize young adults who report problematic internet use. An index of internet addiction as well as measures of traits previously linked to problematic substance use were administered to a sample of 86 young adults aged 18–30 years. Measures included the Internet Addiction Test (IAT), Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ), Depression Anxiety and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
3
27
2
Order By: Relevance
“…Generalisability of the present findings may nevertheless be questioned. TAS‐20 alexithymia scores were unusually high in this Australian sample compared to what has been reported for the general adult population in other countries (e.g., Mattila, Salminen, Nummi, & Joukamaa, ); however, as Qualtrics recruits people online, the sample may have been somewhat biased towards those who spend relatively more of their time online—as highly alexithymic individuals have been reported to do (e.g., Lyvers et al, )—hence, the relatively high overall scores on this trait. AUDIT scores were also high, with the mean score at a level indicative of hazardous drinking (Saunders et al, ), but such scores may be typical for young Australian adults, especially men (e.g., Bowring, Gouillou, Hellard, & Dietze, ).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Generalisability of the present findings may nevertheless be questioned. TAS‐20 alexithymia scores were unusually high in this Australian sample compared to what has been reported for the general adult population in other countries (e.g., Mattila, Salminen, Nummi, & Joukamaa, ); however, as Qualtrics recruits people online, the sample may have been somewhat biased towards those who spend relatively more of their time online—as highly alexithymic individuals have been reported to do (e.g., Lyvers et al, )—hence, the relatively high overall scores on this trait. AUDIT scores were also high, with the mean score at a level indicative of hazardous drinking (Saunders et al, ), but such scores may be typical for young Australian adults, especially men (e.g., Bowring, Gouillou, Hellard, & Dietze, ).…”
Section: Discussioncontrasting
confidence: 42%
“…These associations are typically interpreted by researchers as reflecting use of different means to enhance or reinforce narcissistic feelings of superiority and grandiosity. As mentioned earlier, research has indicated that several other traits are similarly elevated in those with behavioural addictions as in those with substance abuse or addiction, including rash impulsiveness, reward sensitivity, and alexithymia (Kandri et al, ; Lyvers et al, ). Dawe et al () differentiated between reward sensitivity and rash impulsiveness in terms of purported roles as predisposing factors in substance misuse, with the former promoting onset of use and the latter maintaining compulsive use in addiction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The classification of Internet addiction as a behavioral disorder remains a controversial matter. It has been described as an individual's uncontrollable and compulsive use of the Internet, which negatively affects academic and job performances, reduces sleep and hygiene quality, and leads to reduced interpersonal social relationships (Lyvers, Karantonis, Edwards, & Thorberg, 2016;Sahraian, Hedayati, Mani, & Hedayati, 2016;Young, 2015;Zhang et al, 2015). Furthermore, the conceptual model of Internet addiction incorporates tolerance, withdrawal, relapse, salience, conflict and mood modification as the core criteria for symptoms of addictive behavior (McNicol & Thorsteinsson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With this respect, internet addiction can be considered to be closely related to affections. Studies have put forward that internet addiction is related to depression [56][57][58][59], distress [60], happiness [42], hostility [61], irritation and anger [13], loneliness [62,63], shyness [64,65], fear [66], and bipolar disorder [58]. In addition, according to Savci and Aysan, among the attachment style (secure, dismissive, fearful, and preoccupied), peer relationships (companionship, conflict, help, security, and closeness) and positive-negative affection variables negative affection makes the most significant contribution to internet addiction [67].…”
Section: Discussionmentioning
confidence: 99%